Effects of Vitamin D3 on Methotrexate- Induced Jejunum Damage in Rats - Abdul-Wahab, Farah K.; Al-Shawi, Nada N (Iraqi Journal of Pharmaceutical Sciences, 2020)
Both methotrexate and vitamin D3 are used in combination for the treatment of various diseases. The aim of this study is to highlight the effect of vitamin D3 on methotrexate-induced jejunum damage using biochemical and histopathological studies. Seven groups of both sexes of rats were selected and treated as follows: (Group I and Group II) : control 1,control 2 (I.P normal saline) daily for 14 and 21 days respectively ; (Group III and Group IV) :vitamin D3 groups (500 IU/rat/day) orally for 14 and 21 days, respectively;(Group V): once daily dose of methotrexate 20mg/kg, I.P injected for 4 days;(Group VI):vitamin D3 (500 IU/rat/day) once daily for 14 days and methotrexate (20 mg/kg I.P) injected only at day 10;.(Group VII) vitamin D3 (500 IU/rat/day) orally for 21 days and methotrexate (20 mg/kg I.P) injected only at day 17; then the jejunum was removed and used for measuring malondialdehyde (MDA) content, total antioxidant capacity (TAOC) level; in addition histopathological study of jejunum tissue. Administration of vitamin D3 for 21 days and a single dose of methotrexate at day 17 resulted in non-significant difference (P>0.05) in MDA; while significant reduction (P<0.05) in the TAOC level in jejunum tissue; furthermore , sever villi damage ,crypts abscess, epithelial atrophy , mixed inflammatory cells infiltrate and goblet cells depletion were observed in comparison with methotrexate group. So the study demonstrates that vitamin D3 plays a synergistic role with methotrexate therefore the combined use of vitamin D3 and methotrexate may be used as a strategy to overcome dose limitations and side effects when use for the treatment of cancer, rheumatoid arthritis and psoriasis.Key words: Jejunum damage, Methotrexate, Oxidative stress, Rats, Vitamin D3.